RESEARCH ON THE DESIGN OF A NOVEL HIGHYWAY CRASH CUSHION BASED ON THE MINMIAL SURFACE SANDWICH STRUCTURE (MT) - SUN Nan; ZHOU KaiFa; WANG Shuai; MA WenYi; GUO DongLing (Jixie qiangdu)
To solve the problem of excessive collision force caused by traditional crash cushion, a novel guiding crash cushion is designed based on the Singly Periodic Minimal Surface（SPMS） sandwich structure. Firstly, Mathematica is used to explore the influence of parameter changes of a, b and c in the implicit function expression of SPMS on the structure form. Then, the quasi-static compression finite element simulation is carried out. Finally, the vehicle-crash cushion collision model system is established, and the full scale crash simulation is carried out at the speed of 100 km/h. The results show that the change of parameters a and b will make the structure exhibit periodic rotational symmetric changes, and the change of parameter c will change the size of the genus. At last, the optimal values of parameters a, b and c are 1, 0.3 and 0 respectively. Through the full scale crash simulation, compared with the traditional crash cushion, the peak impact force of the novel crash cushion decreases by 37.5% and 18.8% in the frontal and frontal lateral conditions. The new crash cushion can effectively reduce the impact force, and absorb the huge energy under the impact damage, which possesses a good engineering reference value.